Association of sleep-disordered breathing with total healthcare costs and utilization in older men: the Outcomes of Sleep Disorders in Older Men (MrOS Sleep) study. Issue 1 (25th September 2019) - Vo, Tien N; Kats, Allyson M; Langsetmo, Lisa; Taylor, Brent C; Schousboe, John T; Redline, Susan; Kunisaki, Ken M; Stone, Katie L; Ensrud, Kristine E
Abstract: Study Objectives: To determine the associations of sleep-disordered breathing (SDB) with subsequent healthcare costs and utilization including inpatient and post-acute care facility stays among community-dwelling older men. Methods: Participants were 1, 316 men (mean age 76.1 [ SD = 5.7] years) in the Outcomes of Sleep Disorders in Older Men (MrOS sleep) study (from December 2003 to March 2005), who were enrolled in a Medicare Fee-For-Service plan. Primary SDB measures including apnea hypopnea index (AHI) and oxygen desaturation index (ODI) were collected using in-home level 2 polysomnography. Incident healthcare costs and utilization were determined from claims data in the subsequent 3-year period post-MrOS sleep visit. Results: Five hundred and twenty-nine (40.2%) men had at least one hospitalization in the 3-year period. Compared with those without sleep apnea (AHI < 5/hour), men with moderate to severe sleep apnea (AHI ≥ 15/hour) had a higher odds of all-cause hospitalization (odds ratio [OR] adjusted for age and site 1.43, 95% confidence interval [CI]: 1.07–1.90). This association was slightly attenuated after further adjustment for traditional prognostic factors including education, body mass index, comorbid medical conditions, and health status (OR = 1.36; 95% CI: 1.01–1.83). Similar associations were observed for ODI. However, measures of SDB were not related to subsequent healthcare costs (total or outpatient) or odds of post-acute skilled nursing facility stay. Conclusions: Older men with SDB have an increased risk of hospitalization, not entirely explained by the greater prevalence of comorbid conditions, but not higher subsequent total healthcare costs. These findings indicate a need to evaluate the impact of SDB treatment on subsequent healthcare utilization.